Relevansi Konsep ‘Hamba Allah Bersaudara’ dalam Membangun Toleransi dan Keharmonisan dalam Pendidikan Islam - Busthomi, Yazidul; Damanhuri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Brotherhood can exist if it is based on the brotherhood of imaniyah, basyariyah, and wasathoniyah. Humans cannot live alone, apart from being personal creatures, humans are also social creatures. Brotherhood is an essential need. The faithful servants of Allah are brothers as explained in the Qur'an, surah Al-Hujurat verse 10, which means: verily the believers are brothers, therefore make peace between your two brothers and fear Allah so that you may receive mercy. And the Prophet Sallallahu 'alaihi Wasallam said: